18FDG-PET metabolic response of non-small-cell lung cancer to chemoradiotherapy with long-term follow-up. Issue 1 (11th October 2017) - Ampil, Federico; Caldito, Gloria; Richards, Troy
Abstract: Aim: 18 Fluorodeoxyglucose-positron emission tomography (FDG-PET) can indicate the presence or absence of non-small-cell lung cancer (NSCLC) after treatment. We present a description of the FDG-PET results following the contemporary management of locally advanced NSCLC including long-term outcomes. Methodology: The study participants were eight long-term survivors with metabolic tumour response (MTR) shown on FDG-PET following chemoradiotherapy for locally advanced stage NSCLC between June 2005 and April 2009. Results: After therapy, MTR was complete in five patients; four subjects were free of cancer, and one patient experienced progression of disease at the time of last follow-up. Of the three individuals with incomplete MTRs, distant metastases developed in two patients, and one subject remained disease-free. Long-term survival ranged from 37 to 75 months. Conclusion: Although the number of cases is small, our observations confirm the diagnostic role of FDG-PET as well as its value for predicting prognosis in the clinical practice of oncology.